2018
DOI: 10.1016/j.bbi.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Lack of junctional adhesion molecule (JAM)-B ameliorates experimental autoimmune encephalomyelitis

Abstract: In multiple sclerosis (MS) and its animal model experimental autoimmune encephalomyelitis (EAE) autoaggressive CD4 T cells cross the blood-brain barrier (BBB) and cause neuroinflammation. Therapeutic targeting of CD4 T-cell trafficking into the CNS by blocking α4-integrins has proven beneficial for the treatment of MS but comes with associated risks, probably due to blocking CD8 T cell mediated CNS immune surveillance. Our recent observations show that CD8 T cells also rely on α4β1-integrins to cross the BBB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
(121 reference statements)
1
23
0
1
Order By: Relevance
“…We did not detect any differences in plasma; however, EVs depicted a similar difference of JAM-B, as that seen in the study by Whelan et al [ 59 ], where JAM-B was found downregulated in cognitively affected. JAM-B is a tight junction protein expressed by brain endothelial cells forming the BBB [ 60 ], and its dysregulation could be ascribed to the disruption of the BBB [ 61 ]. JAM-B has also been associated with lymphocyte transendothelial migration [ 62 ] and vascular inflammation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not detect any differences in plasma; however, EVs depicted a similar difference of JAM-B, as that seen in the study by Whelan et al [ 59 ], where JAM-B was found downregulated in cognitively affected. JAM-B is a tight junction protein expressed by brain endothelial cells forming the BBB [ 60 ], and its dysregulation could be ascribed to the disruption of the BBB [ 61 ]. JAM-B has also been associated with lymphocyte transendothelial migration [ 62 ] and vascular inflammation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…JAMs are immunoglobulin superfamily transmembrane proteins, with JAM-A and JAM-B being the most studied in BBB endothelial cells. JAM-A contributes to the establishment of cell polarity (22) and both JAM-A and JAM-B have been described to mediate leukocyte trafficking across the BBB (23,24,25,26,27) (summarized in (10)). Tricellular contact points between BBB endothelial cells show localization of tricellulin, which otherwise has only been described in epithelial tricellular junctions.…”
Section: The Blood-brain Barriermentioning
confidence: 99%
“…The crucial role played by α 4 β 1 /VCAM-1 interaction in T-cell arrest on the BBB is highlighted by the fact that blocking α 4 -integrins has been translated into the most effective treatment for relapsing-remitting MS with the humanized monoclonal anti-α 4 integrin antibody natalizumab. In addition to VCAM-1, another endothelial ligand for α 4 β 1 integrin, namely JAM-B has been shown to be involved in CD8 + ( 27 ), but not CD4 + ( 24 ) T-cell migration across the BBB in mouse models.…”
Section: Immune Cell Trafficking Across the Bbb In Neuroinflammationmentioning
confidence: 99%
“…In vitro-treated cells or cells from in vivo-treated mice were stimulated with 50 ng/mL phorbol myristate acetate (PMA; Alexix Biochemicals), 1 mg/mL ionomycin (BioVision, Inc.), and 3.3 μl/5 mL GolgiStop (BD Biosciences) for 4 h at 37°C in 5 mL medium. After stimulation, cells were collected and stained for CD4, CD25, and FoxP3 using the Treg Detection Kit according to manufacturer's protocol (Myltenyi) or for intracellular cytokines (IFN-γ, IL-17, GM-CSF, IL-4, IL-10) and surface markers (CD45, CD4, CD8) as adapted from [16]. For surface staining, cells were incubated with primary antibody (Additional file 6: Table S1) mixes in FACS buffer (DPBS, 2.5% FBS, and 0.1% NaN 3 ) for 30 min on ice.…”
Section: Facs Analysis Of Splenic and Inguinal Lymph Node Lymphocytesmentioning
confidence: 99%